Application For Petty Cash Management - Norung, Muhammad Hazim Muhamad; Kasim, Shahreen; Defni, - (SOTVI, 2020)
Some people currently face into traps of dept and overspending without even realizing it. The feeling of never having enough cash or living paycheck to paycheck can lead serious final problems that can lead into financial difficulties over a lifetime. This study aims to determine how application can manage the financial problems. Specifically, it manages on how you spend your money and get the overview about it. In this application, it uses financial skills such as budgeting, saving and spending. It refers to the strategies technique to determine the use of an individual. To achieve a better understanding on the money management, a report is created to see the whole month transaction such as saving and spending. The report will show the total amount of money spent and where the money is going. You will understand your expenses with the report and create a budget for future expenses. By having good financial skills, you can have a strategy on how you want to manage your money. Creating and sticking to a budget might seem tough to achieve but it helps us to see full transparency our financial situation.